Drawing on difference : art therapy with people who have learning difficulties - Rees, Mair, 1960- (Routledge, 1998)
Drawing on Difference reveals how art therapy can support and validate the emotional and mental health needs of people with learning difficulties. Case studies present work with adults and children with differing degrees of difficulty.